Application of the public-private partnership formula in thermomodernization projects of public buildings in Poland in the years 2009–2020 - Hajdys, Dagmara (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: For over ten years, Poland has observed a systematic use of the public-private partnership (PPP) formula in implementation of investment projects. Local government units are particularly active in this area. One of the self-government’s own tasks is the management of municipal property, including public utility buildings. The implementation of such tasks, in accordance with the European Commission’s recommendations, should be conducted in cooperation between a local government unit and a private entity under a public-private partnership. Aim: The aim of the study is to assess the public-private partnership market in Poland in the context of the implementation of thermomodernization projects of local government public facilities in the years 2009–2020. Results: The market in Poland is generally flattened, as more than 90 per cent of launched projects fall into the local government sector. It is the local authorities that initiate intersectoral cooperation based on the PPP formula. Knowing their local communities, they carry out tasks that meet their needs on the one hand, and respond to climate and energy challenges on the other. This is evidenced by a growing number of projects